Inflammatory and Redox Blood Gene Expression Fingerprint of Severe Obstructive Sleep Apnoea in Patients With Mild Alzheimer’s Disease - Romero-ElKhayat L; Dakterzada F; Huerto R; Carnes-Vendrell A; Mínguez O; Pujol Sabaté M; Targa A; Barbé F; Milanesi E; Dobre M; Manda G; Cuadrado A; et al. (Journal of Inflammation Research)
Leila Romero-ElKhayat,1 Farida Dakterzada,1 Raquel Huerto,1 Anna Carnes-Vendrell,1 Olga Mínguez,2 Montserrat Pujol Sabaté,2 Adriano Targa,3,4 Ferran Barbé,3,4 Elena Milanesi,5,6 Maria Dobre,5 Gina Manda,5 Antonio Cuadrado,5,7– 10 Gerard Piñol-Ripoll1,11 1Unitat de Trastorns Cognitius, Cognition and Behavior Study Group, Universitat de Lleida, IRBLleida, Lleida, 25198, Spain; 2Unitat de Son, Hospital Universitari Santa Maria de Lleida, Lleida, Spain; 3Group of Translational Research in Respiratory Medicine, Hospital Universitari Arnau de Vilanova and Santa Maria, IRBLleida, Lleida, Spain; 4Center for Biomedical Research in Respiratory Diseases Network (CIBERES), Madrid, Spain; 5“Victor Babes” National Institute of Pathology, Bucharest, 050096, Romania; 6Faculty of Medicine, Carol Davila University of Medicine and Pharmacy, Bucharest, 050474, Romania; 7Department of Endocrine Physiology and Nervous System, Instituto de Investigaciones Biomédicas “Alberto Sols” UAM-CSIC, Madrid, 28029, Spain; 8Department of Biochemistry, Faculty of Medicine, Autonomous University of Madrid, Madrid, 28049, Spain; 9Neuroscience Section, Instituto de Investigación Sanitaria La Paz (Idipaz), Madrid, 28046, Spain; 10Centro de Investigación Biomédica en Red Sobre Enfermedades Neurodegenerativas (CIBERNED), ISCIII, Madrid, 28031, Spain; 11Alzheimer’s Disease and Other Cognitive Disorders Unit, Hospital Clínic de Barcelona, Fundació de Recerca Clínic Barcelona – Institut d’Investigacions Biomèdiques August Pi I Sunyer (IDIBAPS), Barcelona, SpainCorrespondence: Gerard Piñol-Ripoll, Cognitive Disorders Unit, Hospital Universitari Santa Maria, Rovira Roure no. 44, Lleida, 25198, Spain, Tel +34-937-727222, Ext. 173, Fax +34-976-727366, Email gerard_437302@hotmail.comIntroduction: Obstructive sleep apnoea (OSA) is the sleep disorder most frequently found in patients with Alzheimer’s disease (AD). The intermittent hypoxia (IH) caused by OSA may participate in AD pathogenesis through increase in oxidative damage and inflammation. We aimed to identify inflammatory and redox genes differentially expressed in the blood from AD patients with severe OSA compared with those with nonsevere OSA.Methods: We included 40 AD patients diagnosed based on clinical manifestations and AD biomarker levels in cerebrospinal fluid (CSF). Severe or nonsevere OSA (apnoea–hypopnea index ≥ 30/h and < 30/h, respectively) was diagnosed through overnight polysomnography (PSG). The expression levels of 136 inflammation-related and 84 redox-related genes were evaluated by whole blood targeted transcriptomics.Results: Three inflammatory and six redox genes were upregulated in the blood of AD patients with severe OSA. Three of them correlated with PSG parameters. A pathway enrichment analysis showed a strong enrichment of the serotonergic synapse pathway in severe OSA AD patients.Discussion: Our results show an upregulation of nine genes involved in NF-κB-mediated inflammation and redox metabolism in the blood of patients with mild AD with severe OSA. Therefore, severe OSA may worsen the inflammation and oxidative damage that are already altered in patients with AD.Keywords: Alzheimer’s disease, obstructive sleep apnea, oxidative stress, inflammation, gene expression, NF-κB signaling